Pro JavaScript Development : Coding, Capabilities, and Tooling - Odell, Den (Apress, 2014)
Pro JavaScript Development is a practical guide for front-end web developers who are experienced at building web pages with HTML, CSS, and JavaScript, and now wish to advance their JavaScript skills to a higher level. You will learn how to build large, well-structured, high quality, mobile-optimized web sites and apps, using the latest supported browser APIs, language features, and tools. This book teaches and shows you in practical hands-on terms how you can: Master the performance, reliability, stability, and code manageability of your JavaScript Understand and write efficient object-oriented and prototypal code, including full understanding of the 'this' keyword Boost the performance of your JavaScript code Architect large web applications using common design patterns Write high quality JavaScript code and avoid the pitfalls most likely to cause errors Manage code dependencies with AMD and RequireJS Develop for mobile, build games, and set up a real-time video chat using modern APIs such as Geolocation, Canvas and WebRTC Document your code as the professionals do Write command-line and web server applications in JavaScript with Node.js, Use build tools, such as Grunt and Gulp, to automate repetitive tasks and improve your development workflow Using real-world examples and applications that you'll build yourself, Pro JavaScript Development has unique, practical content that will make you a better JavaScript developer. Become a master of the latest JavaScript coding techniques and tools, and harness its best capabilities today.